2006
DOI: 10.1021/ie050861m
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Saturation Density from Predictive Correlations Based on the Corresponding States Principle. Part 1:  Results for 30 Families of Fluids

Abstract: Nine empirical correlations for the calculation of the liquid saturation density of pure fluids are studied for their accuracy and applicability. All of them are based on the corresponding states principle, and we have included very recent proposals. The first model requires only the knowledge of critical parameters, the following seven need the critical parameters and acentric factor as inputs, and the last requires the Lennard-Jones molecular parameters and the acentric factor as input data. As a reference, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…In previous papers we have shown that this model gives good results for a large number of fluids of different kinds, but for some of them is not accurate near the triple point [24,25]. More recently [17], we have shown that this model gives an M D of 3.1% when compared with data for 107 fluids from the DIPPR database [26].…”
Section: Saturated Liquid Densitymentioning
confidence: 95%
“…In previous papers we have shown that this model gives good results for a large number of fluids of different kinds, but for some of them is not accurate near the triple point [24,25]. More recently [17], we have shown that this model gives an M D of 3.1% when compared with data for 107 fluids from the DIPPR database [26].…”
Section: Saturated Liquid Densitymentioning
confidence: 95%
“…Bhirud [12], proposed a corresponding states principle correlation for predicting saturated liquid density:…”
Section: The Third Modelmentioning
confidence: 99%
“…For a scientist it is very important to choose the appropriate model for a given class of fluids or even for a particular fluid at a particular temperature (Kolasinska and Vera, 1986;Joback andReid, 1987, Ibrahim andMurad, 1989;Hurst and Harrison, 1992;Mulero et al, 2006aMulero et al, , 2006bMulero et al, , 2006cMulero et al, , 2006dMulero et al, , 2006e, 2010aMulero and Parra, 2008;Cachadiñ a and Mulero, 2009;Miqueu et al, 2000). The most extensively used correlations are based on the corresponding states principle (Poling, 2001;Xiang, 2005).…”
Section: Introductionmentioning
confidence: 99%